SaLudo: a randomized phase IIb/III study of lurbinectedin plus doxorubicin as first-line treatment in leiomyosarcoma - Cote, Gregory M.; Chawla, Sant P.; Demetri, George; Kasper, Bernd; Jones, Robin L.; Broto, Javier Martin; Wooley, Joseph; Weiss, Mia C.; Tafuto, Salvatore; Badalamenti, Giuseppe; Carrasco, Irene; Peinado, Paloma; et al. (Future oncology, 2025)
Previous phase I/II trials indicate promising activity of lurbinectedin plus doxorubicin (DOX) in leiomyosarcoma (LMS). We describe here the rationale and design of SaLuDo, an open label, randomized, multicenter, seamless phase IIb/III study to evaluate the antitumor activity and safety of lurbinectedin plus DOX versus DOX alone in the first-line setting of metastatic LMS. The phase IIb stage will evaluate two schedules of the combination for the phase III stage given every 3 weeks (q3wk): DOX 50 mg/m2 plus lurbinectedin 2.2 mg/m2, and DOX 25 mg/m2 plus lurbinectedin 3.2 mg/m2. The control arm will be DOX 75 mg/m2 q3wk. The primary endpoint is progression-free survival by independent review; overall survival is the key secondary endpoint. Clinical trial registration: www.clinicaltrials.gov identifier is NCT06088290.